Tumor-to-tumor metastasis to Warthin tumor presenting as an initial sign of breast carcinoma: A case report - Mansikka Iisa; Kinnunen Ilpo; Hirvonen Jussi; Vainio Paula; Velhonoja Jarno (WILEY, 2025)
Metastases of distant primary tumors on the parotid gland are very rare. Tumor-to-tumor metastasis to salivary gland tumors is extremely rare. A case of a 69-year-old woman with a large left parotid gland mass with no previous salivary gland problems or cancer. Fine-needle aspiration (FNA) showed evidence of a Warthin tumor. A total left parotidectomy was performed. The final pathology report showed a Warthin tumor containing two metastases of adenocarcinoma. The immunohistochemistry of the metastases led to the diagnosis of primary breast cancer. A negative FNA does not rule out the possibility of a malignant parotid tumor or metastasis, and a parotid lump should be presumed to be a secondary tumor until proven otherwise if the patient has a history of any distant primary cancer. Our patient case serves as a reminder that a new distant primary cancer might be the cause of a parotid lump.